Targeted Fe‐Doping of Ni−Al Catalysts via the Surface Redox Reaction Technique for Unravelling its Promoter Effect in the CO2 Methanation Reaction. Issue 2 (26th November 2019) - Burger, Thomas; Augenstein, Hannah M. S.; Hnyk, Franziska; Döblinger, Markus; Köhler, Klaus; Hinrichsen, Olaf
Abstract: In promoted catalyst systems, the location of dopants is of very high interest to investigate promoter effects. A Ni/Al2 O3 catalyst ( w Ni =11 wt. %) prepared by deposition‐precipitation and a co‐precipitated NiAlOx ( n Ni / n Al =1) catalyst are modified with Fe by means of the surface redox reaction technique and tested for activity under differential and integral conditions and for thermal stability (aging at 500 °C, 8 bar, 32 h) in the methanation reaction of CO2 . By applying detailed material characterization studies comprising H2 and CO2 chemisorption, ICP‐OES, XRD, STEM‐EDX, FMR and BET, it is shown that the surface deposition techniques can be used to selectively deposit Fe in the vicinity of Ni nanoparticles. Doping with Fe leads to an increase of the catalytic activity, attributed to electronic effects through the formation of surface Ni−Fe alloys, and, for the co‐precipitated Ni−Al catalyst, to an enhancement of the apparent thermal stability at higher Fe loadings, which is assumed to be caused by a dynamic variation of Ni, Fe, and Al interactions depending on the reaction conditions. Abstract : It's all coming unraveled : Selective doping of Fe on Ni for improving activity of a supported Ni/Al2 O3 catalyst and apparent thermal stability of a co‐precipitated NiAlOx catalyst in the methanation reaction of CO2 .